Examination of the relationship between the reaction time, competition result with the competition hour in the world indoor championships (2006-2022): 60 meters - Satilmis, N.; Tasdemir, B.; Bayraktar, I.; Bayraktar, A. (Turkish Journal of Sport and Exercise, 2023)
The relationship between the reaction time and the total running time of male (n=407) and female (n=345) athletes competing in the 60-meter wind sprint branch at the world indoor championships between 2006 and 2022 and the competition hour was examined in this study. Statistically significant and negative relationships were found between competition hour and athletes' reaction times, competition hour and athletes' competition result ratings in both genders (rho<0.040; p<0.05). When the subject is examined in terms of the stages of the competitions, no relationship was found for both genders in the final stage while the same relationships were preserved in the semi-final stage. At the qualification stage, a positive relationship was observed between the competition hour and the reaction time in both men (rho=0.25) and women (rho=0.22). In particular, it will be important that the competition time zones in the qualification stage are in similar circadian zones so as not to create a disadvantage among the athletes, and that the competition programs should be prepared by taking the performance-limiting and performance-supporting time zones into account.